Produktivitas Pukat Cincin (Purse seine) Untuk Penangkapan Ikan Cakalang (Katsuwonus pelamis) Di Perairan Kabupaten Boalemo - Muhammad Umsini Putra; Iwan Iwan (Gorontalo Fisheries Journal, 2018)
The purpose of this research is to know the productivity of the purse seine fishing gear, for skipjack (Katsuwonus pelamis) in the waters of Boalemo Regency. This research uses survey method. The results showed the highest CPUE value of skipjack (Katsuwonus pelamis) in 2012 was 9.83 tons / year and the lowest CPUE value in 2011 was 1.50 tons / year. MSY skipjack (Katsuwonus pelamis) is 3,112.45 ton / year but FMSY is only 705,55 trips. The utilization rate of skipjack (Katsuwonus pelamis) in Boalemo Regency waters is only 0.2636%. Keywords : Productivity, Purse seine, Skipjack, Boalemo DistrictÂ